Evaluation of oral hygiene care of under 4 years old children by their mothers based on the Health Belief Model - Baghiani Moghadam, Mohammad Hossein; Mozaffarian Azad, Mahnoosh; Biria, Mina; Sabour, Siamak (Journal of Dental School, 2019)
Objective: Oral health is one of the basic components of preschool children’s health. Young children completely depend on their parents, specially their mothers, to have an appropriate oral health. Health belief model shows the relationship between some structures related to personal perceptions, barriers and perceived self-efficiency, and behavior. This study aims to determine the oral health care status of children under 4 by their mother according to health belief model in Tehran. Methods: In this cross-sectional (descriptive-analytic) study, 200 mothers with children under 4 who visited health care centers under the authority of Shahid Beheshti University of medical Sciences were randomly chosen. A questionnaire which was designed according to health belief model (HBM) was used to collect data. Collected data was analyzed by SPSS software. Results: It was found that only in 10% of the cases knowledge score was favorable. Participants scored 50.85%, 75.93%, 72.23%, 92.06%, 48.2%, 86.31%, 64.07% in knowledge structures, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self efficiency and behavior respectively. Knowledge structures (p<0.01, r=0.276), perceived barriers (p<0/01, r=0/314) and perceived self efficiency (p<0.01, r=0.269) showed positive correspondence and significant relationship with the oral and dental health behaviors by their mothers. Structures of health belief model could describe 17.9% of behavior variance. Amongst these structures, perceived barriers had more important role. Conclusion: This study estimated that the behavioral status of oral and dental health care of children under 4 by their mothers is moderate. Therefore planning an educational program using behavioral models and theories, such as health belief model is suggested, so that it can increase knowledge and self-efficiency and reduce perceptive barriers to promote children’s oral health.